In-situ synthesis Al2O3 reinforced low-density iron-based composite material and preparation method thereof
By directly synthesizing the Al2O3 reinforced phase using in-situ synthesis technology during the casting process, it forms a metallurgical combination with the iron matrix, solving the problems of complex preparation, high cost and insufficient interface strength in the prior art, and achieving material performance improvement and process simplification.
Patent Information
- Application Number
- CN202411599117.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-07
AI Technical Summary
The existing Al2O3 reinforced iron-based composite materials have complex preparation methods, high energy consumption, high cost, and weak interface strength between the reinforced phase and the matrix, which affects the material performance.
In-situ synthesis technology is used to directly synthesize the Al2O3 reinforced phase during the casting process, forming a metallurgical bond with the iron matrix, simplifying the preparation process, reducing costs, and improving interface bonding.
It improves the overall mechanical properties and durability of the material, maintains the lightweight properties of the material, reduces the preparation cost, and simplifies the process flow.
Smart Images

Figure CN119571202A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal-based composite materials, and more specifically to an in-situ self-generated Al2O3-reinforced low-density iron-based composite material and a preparation method thereof. Background Art
[0002] Particle-reinforced iron-based composite materials are made of steel materials with high stiffness, strength and hardness as the matrix and hard particles as the reinforcement phase. The two are compounded through a certain process. They have the good plasticity, toughness, easy processing and electrical and thermal conductivity of the iron matrix, as well as the high hardness, good thermal stability and low expansion coefficient of the hard particles. They meet the needs of modern industry and have good development and application prospects. Among the commonly used iron-based composite ceramic reinforcement particles, the linear expansion coefficient of Al2O3 is the closest to that of Fe (the linear expansion coefficient of Al2O3 is 7.1~8.4×10 -6 / K, the average linear expansion coefficient of steel is 11×10 -6 / K), Al2O3 has excellent wear resistance, high temperature stability and chemical stability, which can enable composite materials to maintain high performance under harsh conditions. In addition, Al2O3 is low in price, high in hardness, good in wear resistance, and has a wide range of raw material sources and price advantages. It is most widely used in industrial production, which makes the large-scale and mass production of Al2O3-reinforced iron-based composites more possible.
[0003] At present, the methods for producing Al2O3 reinforced iron-based composite materials are mainly solid-phase methods such as powder metallurgy and self-propagating high-temperature synthesis. They are usually prepared by mixing the reinforcing phase (such as particles, fibers, etc.) into the matrix material and then sintering or hot pressing. The solid-phase method for preparing composite materials requires multiple steps, such as mixing powders, molding, sintering, etc. The processing process is complicated, and the energy consumption during the preparation process is large, which makes the overall cost high. The difference in the properties of the matrix powder and the reinforcing phase powder may lead to uneven particle distribution, making it difficult to achieve ideal uniform dispersion. The process parameters need to be precisely controlled, which also increases the difficulty of preparation. In the Al2O3 reinforced iron-based composite material prepared by the above solid-phase method, Al2O3 and the matrix are mechanically bonded, and the interface strength is weak, which also affects the final performance of the material.
[0004] The present invention uses in-situ synthesis technology to directly synthesize the required reinforcing phase during the casting process and form a metallurgical bond with the matrix material. This method can avoid the problem of uneven dispersion of the reinforcing phase in the composite material, and can also solve the problem of poor wettability between the ceramic reinforcing phase and the matrix material, thereby improving the overall performance and stability of the material. Summary of the invention
[0005] In view of the defects existing in the prior art, the purpose of the present invention is to provide an in-situ self-generated Al2O3 reinforced low-density iron-based composite material and a preparation method thereof, which utilizes in-situ synthesis technology to produce Al2O3 reinforcing phase by in-situ reaction in the iron matrix, so that the Al2O3 reinforcing phase forms a metallurgical bond with the iron matrix, which helps to improve the overall mechanical properties and durability of the material. The prepared iron-based composite material has the characteristics of low density, which meets the demand for lightweight materials in modern engineering.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] A first aspect of the present invention provides an in-situ self-generated Al2O3-reinforced low-density iron-based composite material, comprising an iron matrix and an Al2O3 reinforcement phase distributed in the iron matrix;
[0008] The Al content in the iron matrix is 6 to 10 wt.%;
[0009] The Al2O3 reinforcement phase is generated by in-situ reaction of oxygen elements in Fe2O3 and aluminum elements in the melt during the smelting process, and the volume percentage of the Al2O3 reinforcement phase in the iron matrix is 1-5%.
[0010] Preferably, the average particle size of the Al2O3 reinforcement phase is less than 5 μm.
[0011] Preferably, the density of the low-density iron-based composite material is 6.8-7.2 g / cm 3 , hardness is 290HV~330HV.
[0012] The second aspect of the present invention provides a method for preparing the in-situ self-generated Al2O3-reinforced low-density iron-based composite material as described in the first aspect of the present invention, comprising the following steps:
[0013] S1, adding pure Fe and pure Al into an induction furnace for smelting, and casting to obtain a precast ingot after the smelting is completed;
[0014] S2, mixing Fe powder, Al powder and Fe2O3 powder uniformly, and forming a prefabricated block by cold pressing;
[0015] S3, adding the precast ingot into the induction furnace, adding the prefabricated block into the melt after the precast ingot is completely melted, and pouring the prefabricated block after the prefabricated block is completely melted and reacted, so as to obtain an in-situ self-generated Al2O3 reinforced low-density iron-based composite material.
[0016] Preferably, in the step S1: in the pure Fe and pure Al, the Al content is 6-10% of the total mass of the pure Fe and pure Al.
[0017] Preferably, in step S1, during the smelting process in the induction furnace, the melting temperature is controlled to be 1500-1600° C. and the stirring speed is controlled to be 300-360 rpm.
[0018] Preferably, in step S2:
[0019] The mass ratio of the Fe powder, Al powder and Fe2O3 powder is 80-87:10-15:3-5;
[0020] The Fe powder, Al powder and Fe2O3 powder are mixed evenly in a ball mill and then placed in a drying oven for later use.
[0021] Preferably, in step S3, the amount of the prefabricated block added is 9% to 13% of the mass of the precast ingot.
[0022] Preferably, in step S3, after the precast ingot is added to the induction furnace, the melting temperature is controlled to be 1500-1600°C, and the melt temperature after melting is 1500-1550°C.
[0023] Preferably, in step S3, after the prefabricated block is added to the melt, the melt is allowed to stand for 3 to 10 minutes and stirred at a speed of 300 to 360 rpm.
[0024] The beneficial effects of the present invention are as follows:
[0025] 1. The present invention strengthens the low-density iron-based composite material by in-situ self-generated Al2O3, which can effectively improve the comprehensive performance of the composite material; the hardness, wear resistance and high-temperature stability of the material are enhanced by the introduction of Al2O3 particles, while maintaining the lightweight characteristics of the material;
[0026] 2. Compared with the mechanical bonding between the reinforcement phase and the matrix in the preparation of iron-based composite materials by general powder metallurgy methods, the present invention adopts in-situ synthesis technology to prepare iron-based composite materials during the casting process, which effectively improves the wettability of the Al2O3 reinforcement phase and the iron matrix, so that they form a metallurgical bond. This good interface bonding helps to improve the overall mechanical properties and durability of the material;
[0027] 3. Compared with other preparation methods of iron-based composite materials, the in-situ self-generation technology adopted in the present invention can not only simplify the preparation process, but also reduce the preparation cost. Al2O3 particles are generated in-situ during the preparation process, avoiding the subsequent addition steps, thereby saving production costs;
[0028] 4. The in-situ self-generated Al2O3-reinforced low-density iron-based composite material prepared by the present invention has a density 5% to 13% lower than that of conventional steel materials, and has the characteristics of low density, which meets the demand for lightweight materials in modern engineering; this lightweight advantage can reduce the weight of the structure, improve the efficiency of material use and energy utilization, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic flow chart of a method for preparing an in-situ self-generated Al2O3-reinforced low-density iron-based composite material of the present invention;
[0030] Figure 2 1 is a SEM-EDS image of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material prepared in Example 1 of the present invention, (a) is a SEM image of the low-density iron-based composite material, (b) is an O element distribution image in the low-density iron-based composite material, and (c) is an Al element distribution image in the low-density iron-based composite material;
[0031] Figure 3 are hardness indentation diagrams of materials, (a) is a hardness indentation diagram of a high-aluminum low-density steel without adding Al2O3 reinforcement phase or other types of reinforcement phases, (b) is a hardness indentation diagram of an in-situ self-generated Al2O3-reinforced low-density iron-based composite material prepared in Example 1 of the present invention;
[0032] Figure 4 This is a hardness indentation SEM image of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material prepared in Example 1 of the present invention;
[0033] Figure 5 This is a macroscopic morphology of the matrix and reinforcement phase of the Al2O3 reinforced iron-based composite material prepared in Comparative Example 1;
[0034] Figure 6 is a microstructure diagram of the Al2O3 reinforced iron-based composite material prepared in Comparative Example 2;
[0035] Figure 7 is a SEM image of the in-situ self-generated Al2O3 reinforced low-density iron-based composite material prepared in Comparative Example 3;
[0036] Figure 8 This is a SEM image of the in-situ self-generated Al2O3 reinforced low-density iron-based composite material prepared in Comparative Example 4. DETAILED DESCRIPTION
[0037] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0038] The present invention provides an in-situ self-generated Al2O3 reinforced low-density iron-based composite material, comprising an iron matrix and an Al2O3 reinforcement phase distributed in the iron matrix; the Al content in the iron matrix is 6-10wt.%; the Al2O3 reinforcement phase is generated by in-situ reaction of oxygen elements in Fe2O3 and aluminum elements in the melt during smelting, and the volume percentage of the Al2O3 reinforcement phase in the iron matrix is 1-5%.
[0039] The average particle size of the Al2O3 reinforcement phase is less than 5 μm. In a preferred embodiment, the average particle size of the Al2O3 reinforcement phase is 3 to 5 μm.
[0040] The density of the above-mentioned in-situ self-generated Al2O3-reinforced low-density iron-based composite material is 6.8-7.2 g / cm 3 , hardness is 290HV~330HV.
[0041] Combination Figure 1 As shown, the preparation method of the above-mentioned in-situ self-generated Al2O3 reinforced low-density iron-based composite material comprises the following steps:
[0042] S1, adding pure Fe and pure Al into an induction furnace for smelting, and casting to obtain a precast ingot after the smelting is completed;
[0043] In this step, pure Fe and pure Al are added into an induction furnace, melted to obtain a melt, and cast to obtain a precast ingot with a thickness of 15 to 20 mm. The pure Fe and pure Al used above can be block materials with a size of about 6 mm × 3 mm × 3 mm; in the pure Fe and pure Al, the Al content is 6 to 10% of the total mass of the pure Fe and pure Al.
[0044] In the above process, pure Fe and pure Al are added into the furnace, and the melt is stirred after melting. At this time, the melt temperature is 1500-1600°C, and the stirring speed is 300-360 rpm. Then, the precast ingot is cast in a graphite ingot mold.
[0045] S2, mixing Fe powder, Al powder and Fe2O3 powder uniformly, and forming a prefabricated block by cold pressing;
[0046] In this step, without destroying the original properties of the matrix powder, Fe powder, Al powder and Fe2O3 powder are mixed evenly in a ball mill, and then placed in a drying oven for standby use. The dried mixed powder is made into a prefabricated block by cold pressing at room temperature. The mass ratio of Fe powder, Al powder and Fe2O3 powder is 80-87:10-15:3-5.
[0047] S3, adding the precast ingot into the induction furnace, adding the prefabricated block into the melt after it is completely melted, and pouring the prefabricated block after it is completely melted and reacted, so as to obtain an in-situ self-generated Al2O3 reinforced low-density iron-based composite material.
[0048] In this step, the precast ingot prepared in step S1 is added to an induction furnace, the melting temperature is controlled to be 1500-1600°C, and the melt temperature after melting is 1500-1550°C; after the precast ingot is completely melted, the prefabricated block obtained in step S2 is added to the melt, and the melt is allowed to stand for 3-10 minutes, and the melt is stirred at a stirring speed of 300-360 rpm. After the prefabricated block is completely melted and reacted, it is poured to obtain an in-situ self-generated Al2O3-reinforced low-density iron-based composite material.
[0049] In the above process, the amount of prefabricated blocks added is 9% to 13% of the mass of the precast ingot.
[0050] In this step, an in-situ synthesis technique is used to generate an Al2O3 reinforcement phase by in-situ reaction during the smelting process, and finally an in-situ self-generated Al2O3-reinforced low-density iron-based composite material is obtained, wherein the volume percentage of the Al2O3 reinforcement phase in the iron matrix is 1-5%.
[0051] The density of the low-density iron-based composite material is 6.8-7.2 g / cm 3 , hardness is 280HV~330HV.
[0052] The in-situ self-generated Al2O3 reinforced low-density iron-based composite material and its preparation method of the present invention are further described below in conjunction with specific embodiments.
[0053] Example 1
[0054] The preparation method of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material of this embodiment is as follows:
[0055] Step 1: Weigh 90g of pure Fe and 10g of pure Al, where the Al content is 10% of the total mass of pure Fe and pure Al, add the pure Fe and pure Al into an induction furnace, stir the melt after melting, at this time, the melt temperature is 1520°C, the stirring speed is 300 rpm, and the melt is obtained after melting, and poured into a graphite ingot mold to finally obtain a precast ingot with a thickness of 15mm;
[0056] Step 2: Weigh 9 g of Fe powder, Al powder and Fe2O3 powder in a mass ratio of 87:10:3, mix the three raw materials evenly in a ball mill without destroying the original properties of the matrix powder, and place them in a drying oven for later use; the dried mixed powder is made into a prefabricated block by cold pressing at room temperature.
[0057] Step 3: Load the precast ingot obtained in step 1 into an induction melting furnace, control the melting temperature to 1600°C, and the melt temperature after melting is 1550°C. Then add the prefabricated block obtained in step 2, the mass of the prefabricated block is 9% of the mass of the precast ingot, let it stand for 10 minutes after adding the prefabricated block, stir the melt, the stirring speed is 360 rpm, and pour it after it is completely melted to obtain a low-density iron-based composite material with Al2O3 reinforcement phase distributed in the matrix.
[0058] As shown in Table 1, the Al content in the iron matrix of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material prepared in this embodiment is 10wt.%. In the low-density iron-based composite material, the volume percentage of the Al2O3 reinforcement phase is 3%, and the average particle size of the Al2O3 reinforcement phase is 3μm; the overall density of the low-density iron-based composite material is 6.91g / cm 3 , hardness is 298.1HV.
[0059] Figure 2 The SEM-EDS image of the low-density iron-based composite material prepared in this embodiment is shown in FIG. Figure 2 As can be seen from (a), (b), and (c), high-density formed specimens can be prepared under this process parameter. A certain amount of Al2O3 reinforcement phase is distributed in the iron matrix, of which the volume percentage of Al2O3 reinforcement phase is 3%, the average particle size of Al2O3 reinforcement phase is 3μm, and the overall density of the low-density iron-based composite material is 6.91g / cm 3 .
[0060] Figure 3 (a) is the hardness indentation of high aluminum low density steel without adding Al2O3 reinforcement phase or other types of reinforcement phase. Figure 3 (b) is the hardness indentation of the low-density iron-based composite material prepared in this embodiment. Compared with the unreinforced material, the hardness of the low-density iron-based composite material prepared in this embodiment is increased from 241.5 HV to 141.5 HV. 0.3 Increased to 298.1HV 0.3 , an increase of 23.4%.
[0061] Figure 4 This is a hardness indentation SEM image of the low-density iron-based composite material prepared in this embodiment. From the image, it can be seen that under the action of the indenter, there is no separation or shedding trend at the interface between the reinforcing phase Al2O3 and the matrix at the indentation boundary, no cracking, and good interface bonding.
[0062] Example 2
[0063] The preparation method of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material of this embodiment is as follows:
[0064] Step 1: weigh 91g of pure Fe and 9g of pure Al, where the Al content is 9% of the total mass of pure Fe and pure Al, add the pure Fe and pure Al into an induction furnace, stir the melt after melting, at this time, the melt temperature is 1550°C, the stirring speed is 300 rpm, and the melt is obtained after melting, and poured into a graphite ingot mold to finally obtain a precast ingot with a thickness of 17 mm;
[0065] Step 2: Weigh 10 g of Fe powder, Al powder and Fe2O3 powder in a mass ratio of 85:11:4, mix the three raw materials evenly in a ball mill without destroying the original properties of the matrix powder, and place them in a drying oven for later use; the dried mixed powder is made into a prefabricated block by cold pressing at room temperature.
[0066] Step 3: The precast ingot obtained in step 1 is loaded into an induction melting furnace, the melting temperature is controlled to be 1580°C, the melt temperature after melting is 1530°C, and then the prefabricated block obtained in step 2 is added, the mass of the prefabricated block is 10% of the mass of the precast ingot, and after adding the prefabricated block, it is allowed to stand for 8 minutes, and the melt is stirred at a stirring speed of 300 rpm. After all the melt is poured, a low-density iron-based composite material with Al2O3 reinforcement phase distributed in the matrix is obtained.
[0067] As shown in Table 1, the Al content in the iron matrix of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material prepared above is 9wt.%, and a certain amount of Al2O3 reinforcement phase is distributed in the iron matrix, wherein the volume percentage of the Al2O3 reinforcement phase is 1.5%, the average particle size of the Al2O3 reinforcement phase is 3.6μm, and the overall density of the low-density iron-based composite material is 7.04g / cm 3 , hardness is 310HV.
[0068] Example 3
[0069] The preparation method of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material of this embodiment is as follows:
[0070] Step 1: weigh 92g of pure Fe and 8g of pure Al, where the Al content is 8% of the total mass of pure Fe and pure Al, add the pure Fe and pure Al into an induction furnace, stir the melt after melting, at this time, the melt temperature is 1580°C, the stirring speed is 340 rpm, and the melt is obtained after melting, and poured into a graphite ingot mold to finally obtain a precast ingot with a thickness of 19 mm;
[0071] Step 2: Weigh 11 g of Fe powder, Al powder and Fe2O3 powder in a mass ratio of 80:15:5, mix the three raw materials evenly in a ball mill without destroying the original properties of the matrix powder, and place them in a drying oven for later use; the dried mixed powder is made into a prefabricated block by cold pressing at room temperature.
[0072] Step 3: The precast ingot obtained in step 1 is loaded into an induction melting furnace, the melting temperature is controlled to be 1550°C, the melt temperature after melting is 1520°C, and then the prefabricated block obtained in step 2 is added, the mass of the prefabricated block is 11% of the mass of the precast ingot, and after adding the prefabricated block, it is allowed to stand for 6 minutes, and the melt is stirred at a stirring speed of 340 rpm. After all the melt is poured, a low-density iron-based composite material with Al2O3 reinforcement phase distributed in the matrix is obtained.
[0073] As shown in Table 1, the Al content in the iron matrix of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material prepared above is 8wt.%, and a certain amount of Al2O3 reinforcement phase is distributed in the iron matrix, wherein the volume percentage of the Al2O3 reinforcement phase is 2.7%, the average particle size of the Al2O3 reinforcement phase is 4.1μm, and the overall density of the low-density iron-based composite material is 7.11g / cm 3 , hardness is 312.6HV.
[0074] Example 4
[0075] The preparation method of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material of this embodiment is as follows:
[0076] Step 1: weigh 94g of pure Fe and 6g of pure Al, where the Al content is 6% of the total mass of pure Fe and pure Al, add the pure Fe and pure Al into an induction furnace, stir the melt after melting, at this time, the melt temperature is 1600°C, the stirring speed is 340 rpm, and the melt is obtained after melting, and poured into a graphite ingot mold to finally obtain a precast ingot with a thickness of 20 mm;
[0077] Step 2: Weigh 13 g of Fe powder, Al powder and Fe2O3 powder in a mass ratio of 80:15:5, mix the three raw materials evenly in a ball mill without destroying the original properties of the matrix powder, and place them in a drying oven for later use; the dried mixed powder is made into a prefabricated block by cold pressing at room temperature.
[0078] Step 3: Load the precast ingot obtained in step 1 into an induction melting furnace, control the melting temperature to 1510°C, and the melt temperature after melting is 1500°C. Then add the prefabricated block obtained in step 2, the mass of the prefabricated block is 13% of the mass of the precast ingot, let it stand for 3 minutes after adding the prefabricated block, stir the melt, the stirring speed is 320 rpm, and pour it after all are melted to obtain a low-density iron-based composite material with Al2O3 reinforcement phase distributed in the matrix.
[0079] As shown in Table 1, the Al content in the iron matrix of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material prepared above is 6wt.%, and a certain amount of Al2O3 reinforcement phase is distributed in the iron matrix, wherein the volume percentage of the Al2O3 reinforcement phase is 4.4%, the average particle size of the Al2O3 reinforcement phase is 4.8μm, and the overall density of the low-density iron-based composite material is 7.20g / cm 3 , hardness is 316.5HV.
[0080] Comparative Example 1
[0081] This comparative example adopts the extrusion casting method to prepare the Al2O3 reinforced iron-based composite material, and its preparation process is as follows:
[0082] (1) Al2O3 with a particle size of 15 to 25 μm is selected as the reinforcement phase and low-carbon steel is selected as the matrix. Al2O3 ceramic particles (95%) + water glass (5%) are placed in a ball mill and evenly mixed, and then pressed into a 90 mm × 6 mm thick preform under a certain pressure. The reinforcement phase preform is preheated to a certain temperature and placed in a mold with a thermal insulation ceramic layer. Then, low-carbon steel metal melt is poured into it. The low-carbon steel metal melt is infiltrated into the reinforcement phase preform by a conventional extrusion casting method to form an Al2O3 reinforced iron-based composite material.
[0083] As shown in Table 1, the Al2O3 reinforced iron-based composite material prepared in this comparative example uses low carbon steel as the matrix material, the Al element is mainly concentrated in the Al2O3 reinforcement phase, the volume percentage of Al2O3 reinforcement particles is 4.3%, the average particle size is about 15 μm, and the density of the Al2O3 reinforced iron-based composite material is 7.65 g / cm 3 , hardness is 160HV. Figure 5 As shown, there is a mechanical bond between the Al2O3 reinforcement particles and the matrix, the interface strength is low, and the reinforcement phase particles are large, which can easily become the origin of cracks and affect the overall strength and performance of the material.
[0084] Comparative Example 2
[0085] This comparative example adopts the melt-casting method to prepare the Al2O3 reinforced iron-based composite material, and its preparation process is as follows:
[0086] 3wt.% Al2O3 powder (purity 95.9%) and low carbon steel were melted in a vacuum water-cooled copper crucible non-consumable arc furnace at a melting voltage of 26V and a melting current of 300-400A. The melting amount was 60g each time, and each sample was melted four times.
[0087] As shown in Table 1, the Al2O3 reinforced iron-based composite material prepared in this comparative example uses low carbon steel as the matrix material, the Al element is mainly concentrated in the Al2O3 reinforcement phase, the volume percentage of Al2O3 reinforcement particles is 1.1%, the average particle size is 3 μm, and the density of the Al2O3 reinforced iron-based composite material is 7.72 g / cm 3 , hardness is 170HV. Figure 6 The microstructure diagram shown shows that the Al2O3 reinforcement phase has uneven particle size and distribution, and low content, which does not provide a good reinforcement effect. The reinforcement phase is mostly located at the grain boundary, which easily becomes a crack source, resulting in reduced fracture toughness, making the material more likely to break under impact load or fatigue load. The reinforcement phase at the grain boundary will increase the brittleness of the material, making it more likely to crack or peel off during subsequent processing, affecting the processing quality.
[0088] Comparative Example 3
[0089] This comparative example adopts the preparation method of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material of Example 1, and the differences from Example 1 are as follows:
[0090] In step 1, 96 g of pure Fe and 4 g of pure Al are weighed, and the Al content is 4% of the total mass of pure Fe and pure Al;
[0091] In step 2, weigh 7 g of Fe powder, Al powder and Fe2O3 powder in a mass ratio of 76:16:8.
[0092] Figure 7 From the SEM image of the in-situ self-generated Al2O3 reinforced low-density iron-based composite material prepared in this comparative example, it can be observed that the Al2O3 reinforcement phase in the sample is unevenly distributed and has a small amount, which does not achieve a good reinforcement effect.
[0093] As shown in Table 1, the Al content in the iron matrix of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material prepared in this comparative example is 4.8wt.%, and a certain amount of Al2O3 reinforcement phase is distributed in the iron matrix, wherein the volume percentage of the Al2O3 reinforcement phase is 0.86%, the average particle size of the Al2O3 reinforcement phase is 5.3μm, and the overall density of the low-density iron-based composite material is 7.42g / cm 3 , hardness is 251HV.
[0094] Comparative Example 4
[0095] This comparative example adopts the preparation method of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material of Example 1, and the differences from Example 1 are as follows:
[0096] In step 1, 87 g of pure Fe and 13 g of pure Al were weighed, and the Al content was 13% of the total mass of pure Fe and pure Al;
[0097] In step 2, weigh 15 g of Fe powder, Al powder and Fe2O3 powder in a mass ratio of 70:18:12.
[0098] Figure 8 From the SEM image of the in-situ self-generated Al2O3 reinforced low-density iron-based composite material prepared in this comparative example, it can be seen that the Al2O3 reinforcement phase has serious aggregation, and the average particle size is large, and the interface bonding with the iron matrix is poor. During the hardness test, the Al2O3 reinforcement phase will desorb from the matrix under the action of the indenter, resulting in a decrease in hardness, which will also seriously affect the comprehensive mechanical properties of the composite material.
[0099] As shown in Table 1, the Al content in the iron matrix of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material prepared in this comparative example is 14.4wt.%, and a certain amount of Al2O3 reinforcement phase is distributed in the iron matrix, wherein the volume percentage of the Al2O3 reinforcement phase is 32.4%, the average particle size of the Al2O3 reinforcement phase is 25.4μm, and the overall density of the low-density iron-based composite material is 6.35g / cm 3 , hardness is 264HV.
[0100] Table 1
[0101]
[0102]
[0103] Combining Table 1, the embodiments and the comparative examples, it can be seen that the Al content in the iron matrix of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material prepared in the embodiment of the present invention is in the range of 6-10wt.%, the volume percentage of the Al2O3 reinforcement phase is 1-5%, the average particle size of the Al2O3 reinforcement phase is 3-5μm, and the overall density of the material is 6.8-7.2g / cm 3 , and the hardness is 280HV~330HV. It can be seen that the method of the present invention utilizes in-situ synthesis technology to produce Al2O3 reinforcement phase in the iron matrix by in-situ reaction, so that the Al2O3 reinforcement phase and the iron matrix form a metallurgical bond with high interface strength, which can improve the hardness of the material while maintaining the lightweight characteristics of the material.
[0104] In summary, the present invention can effectively improve the comprehensive performance of the composite material by the preparation method of the in-situ self-generated Al2O3 reinforced low-density iron-based composite material; the introduction of Al2O3 particles enhances the hardness, wear resistance and high temperature stability of the material, while maintaining the lightweight characteristics of the material. Compared with the mechanical bonding between the reinforcing phase and the matrix in the preparation of iron-based composite materials by general powder metallurgy methods, the present invention adopts in-situ synthesis technology to prepare iron-based composite materials during the casting process, effectively improving the wettability of Al2O3 and the iron matrix, so that they form a metallurgical bond. This good interface bonding helps to improve the overall mechanical properties and durability of the material. Compared with other preparation methods of iron-based composite materials, the in-situ self-generated technology adopted in the present invention can not only simplify the preparation process, but also reduce the preparation cost. Al2O3 particles are generated in situ during the preparation process, avoiding subsequent addition steps, thereby saving production costs. The iron-based composite material prepared by the present invention has a density reduction of 5% to 13% compared with conventional steel materials, has the characteristics of low density, and meets the demand for lightweight materials in modern engineering. This lightweight advantage can reduce the weight of the structure, improve the efficiency of material use and energy utilization, and has a wide range of application prospects.
[0105] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.
Claims
1. An in-situ Al2O3 reinforced low-density iron-based composite material, characterized in that: It includes an iron matrix and an Al2O3 reinforcement phase distributed in the iron matrix; The Al content in the iron matrix is 6 to 10 wt.%; The Al2O3 reinforcement phase is generated by in-situ reaction of oxygen elements in Fe2O3 and aluminum elements in the melt during the smelting process, and the volume percentage of the Al2O3 reinforcement phase in the iron matrix is 1-5%.
2. The in-situ self-generated Al2O3-reinforced low-density iron-based composite material according to claim 1, characterized in that: The average particle size of the Al2O3 reinforcement phase is less than 5 μm.
3. The in-situ self-generated Al2O3 reinforced low-density iron-based composite material according to claim 1, characterized in that: The density of the low-density iron-based composite material is 6.8-7.2 g / cm 3 , hardness is 280HV~330HV.
4. A method for preparing an in-situ Al2O3-reinforced low-density iron-based composite material as claimed in claims 1 to 3, characterized in that: The following steps are involved: S1, adding pure Fe and pure Al into an induction furnace for smelting, and casting to obtain a precast ingot after the smelting is completed; S2, mixing Fe powder, Al powder and Fe2O3 powder uniformly, and forming a prefabricated block by cold pressing; S3, adding the precast ingot into the induction furnace, adding the prefabricated block into the melt after the precast ingot is completely melted, and pouring the prefabricated block after the prefabricated block is completely melted and reacted, so as to obtain an in-situ self-generated Al2O3 reinforced low-density iron-based composite material.
5. The method for preparing the in-situ self-generated Al2O3-reinforced low-density iron-based composite material according to claim 4, characterized in that: In the step S1: in the pure Fe and pure Al, the Al element content is 6-10% of the total mass of the pure Fe and pure Al.
6. The method for preparing the in-situ self-generated Al2O3-reinforced low-density iron-based composite material according to claim 4, characterized in that: In the step S1, during the smelting process in the induction furnace, the melting temperature is controlled to be 1500-1600° C. and the stirring speed is controlled to be 300-360 rpm.
7. The method for preparing the in-situ self-generated Al2O3-reinforced low-density iron-based composite material according to claim 4, characterized in that: In step S2: The mass ratio of the Fe powder, Al powder and Fe2O3 powder is 80-87:10-15:3-5; The Fe powder, Al powder and Fe2O3 powder are mixed evenly in a ball mill and then placed in a drying oven for later use.
8. The method for preparing the in-situ self-generated Al2O3-reinforced low-density iron-based composite material according to claim 4, characterized in that: In the step S3, the amount of the prefabricated block added is 9% to 13% of the mass of the precast ingot.
9. The method for preparing the in-situ self-generated Al2O3-reinforced low-density iron-based composite material according to claim 4, characterized in that: In the step S3, after the precast ingot is added into the induction furnace, the melting temperature is controlled to be 1500-1600°C, and the melt temperature after melting is 1500-1550°C.
10. The method for preparing the in-situ self-generated Al2O3-reinforced low-density iron-based composite material according to claim 4, characterized in that: In the step S3, after the prefabricated block is added to the melt, the melt is allowed to stand for 3 to 10 minutes and stirred at a speed of 300 to 360 revolutions per minute.
Citation Information
Cited By
In-situ synthesis Al2O3 reinforced composite low-density steel and thermal deformation method thereof
CN121737581A